1992
DOI: 10.1111/j.1439-0450.1992.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the API Coryne Test System for Identification of Actinomyces pyogenes

Abstract: The present study was designed to evaluate the accuracy of the API Coryne test system for identification of Actinomyces pyogenes. The test system correctly identified 36 of 42 A.pyogenes and 4 of 5 comparatively studied Arcunobacterzum huemolyticum-cultures. The biochemical profiles of the remaining 6 A.pyogenes-and 1 A. huemo[yticum-cultures were not included in the analytical profile index. None of the cultures were misidentified. According to the API database (ATB Plus V 1.5.4.) the unidentified cultures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…The biochemical properties of the seven A. haemolyticum strains determined with the API Coryne test system are summarized in Table 2. The results corresponded to previous findings (10). The accuracy of the API Coryne test system for identification of A. haemolyticum has already been demonstrated (11,12).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The biochemical properties of the seven A. haemolyticum strains determined with the API Coryne test system are summarized in Table 2. The results corresponded to previous findings (10). The accuracy of the API Coryne test system for identification of A. haemolyticum has already been demonstrated (11,12).…”
Section: Resultssupporting
confidence: 80%
“…The A. haemolyticum cultures were additionally cultivated on Loeffler agar (2) and for determination of cross-reactions with streptococcal serogroup G-specific antisera investigated with a commercial grouping kit (streptococcal identification kit; Oxoid, Wesel, Germany). For biochemical characterization, the API Coryne test system (Biomerieux, Nürtingen, Germany) was used according to the instructions of the manufacturer as described previously (10). In addition, tablets containing substrates for investigation of the enzymes alkaline phosphatase, ␣-mannosidase, and pyrrolidonyl arylamidase (Inverness Medical, Köln, Germany) were used according to the instructions of the manufacturer (Rosco Diagnostica A/S, Taastrup, Denmark).…”
mentioning
confidence: 99%
“…Two studies (27,39) have examined the ability of the API Coryne system (bioMerieux-Vitek) to identify strains of A.…”
Section: Gram-negative Bacillimentioning
confidence: 99%
“…Ding and Lammler (27) determined that 36 of 42 A. pyogenes strains were correctly identified with the API Coryne system, with the remaining six strains yielding unlisted profile numbers. These workers concluded that while the system facilitated identification of A. pyogenes, an improved data base was needed to enhance accuracy.…”
Section: Gram-negative Bacillimentioning
confidence: 99%
See 1 more Smart Citation